Have the NMC educational standards become overly adult-centric?. (10th June 2021) - Glasper, Alan; Fallon, Debbie
Abstract : Emeritus Professor Alan Glasper, from the University of Southampton, and Debbie Fallon, Chair of the Children's and Young People's Nursing Academics of the United Kingdom group, explore concerns raised by academic nurses regarding the Nursing and Midwifery Council standards for pre-registration nursing education